The Effect of Averaging Components on the Predictability of the Index of Consumer Sentiment - Thomas, R. William (The Review of Economics and Statistics, 1975)
T HE Index of Consumer Sentiment is one of the oldest and most respected measures of consumer psychology. The contribution of the Index to the prediction of aggregate consumer durable spending was first examined by Mueller and Katona (1953, 1957). The Index has been used in several econometric models of the U.S. economy (Friend and Taubman, 1964; Duesenberry et al., 1965; Evans, Klein and Schink, 1967). However, the contribution of the Index is only marginally significant in most of these studies, if account is taken of stocks of durables and relative prices. Friend and Adams (1964) have noted that several cyclical variables the average work week in manufacturing, stock market prices, and the unemployment rate -appear to be close substitutes for the Index in automobile demand equations, yielding approximately-equal coefficients of determination when specified with similar lag structures. More recently, Burch and Stekler (1969) compared forecasts of consumer durable expenditure based on income and attitudes with those generated by naive strategies. The use of a serial correlation correction of the error term proved necessary to generate forecasts superior to an assumption of no change in durable sales. Even so, the best fitting equation they estimated was unable to forecast turning points. Thus, the recent evidence suggests to many econometricians that attempting to use expectational variables in large scale econometric models is more trouble than it's worth.1 This is especially true since more convenient variables, such as the unemployment rate, or the average work week in manufacturing, appear to substitute so well. Saul Hymans expressed this sentiment accurately: